2015
DOI: 10.1007/s10654-015-0092-8
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol, drinking pattern and all-cause, cardiovascular and alcohol-related mortality in Eastern Europe

Abstract: Alcohol has been implicated in the high mortality in Central and Eastern Europe but the magnitude of its effect, and whether it is due to regular high intake or episodic binge drinking remain unclear. The aim of this paper was to estimate the contribution of alcohol to mortality in four Central and Eastern European countries. We used data from the Health, Alcohol and Psychosocial factors in Eastern Europe is a prospective multi-centre cohort study in Novosibirsk (Russia), Krakow (Poland), Kaunas (Lithuania) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
60
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 33 publications
9
60
1
1
Order By: Relevance
“…Consistent with other studies [27][28][29], we found that the drinking status was significantly different between men and women. Men had higher rate of alcohol consumption per day and a higher prevalence of being heavy drinkers than women.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with other studies [27][28][29], we found that the drinking status was significantly different between men and women. Men had higher rate of alcohol consumption per day and a higher prevalence of being heavy drinkers than women.…”
Section: Discussionsupporting
confidence: 92%
“…However, our final analysis using multivariate logistic regression showed that, after fully adjusting the data, only heavydrinking participants had an approximately 1.3-fold greater risk for CHD compared with the non-drinking group and that there was no significant association between moderate drinking and CHD. This result is consistent with other studies based on large populations [34,35]. More prospective studies with long-term follow-up periods are needed to confirm these trends.…”
Section: Discussionsupporting
confidence: 92%
“…In Russia, hazardous drinking patterns have been implicated both in the mortality crisis of the 1990s and high long‐term mortality . Our findings support and extend this hypothesis, in that they suggest that drinking pattern is associated with mortality in Russia, Belarus and Hungary in both genders, and particularly when it also includes binge drinking.…”
Section: Discussionsupporting
confidence: 83%
“…To reduce biases associated with long recall periods and changing time trends, the follow‐up was restricted to the last 16 years. Our prevalence estimates of frequent drinking and abstention appear lower and higher than in some other studies in Eastern Europe, but estimates of binge drinking prevalence were broadly similar . In addition, the distributions of alcohol drinking were similar throughout the countries in our study, suggesting that the method performs adequately.…”
Section: Discussionsupporting
confidence: 61%
“…Alcohol intake was assessed using the Graduated Frequency Questionnaire. 22 History of doctor-diagnosed CVD and cancer with and without hospitalisation were coded as dichotomous variables.…”
Section: Methodsmentioning
confidence: 99%